Design and Production of an Animated Short for CD-Rom and Internet. - Bills, Mitchell (Fall;Art., 1998)
Keywords: dept.art; faculty_collection; sabbatical_report

Pre-Columbian. - Zeidenbergs, Olafs (1997)
Keywords: dept.art; faculty_collection; sabbatical_report

Dutch Artists of the 17th Century. - Levine, David (Spring; Art., 1995)
Keywords: dept.art; faculty_collection; sabbatical_report

Greater New Haven shopkeepers. - Cyr, Don (1990)
Keywords: dept.art; faculty_collection; sabbatical_report

Assemblage art. - Guagliumi, Arthur (1990)
Keywords: dept.art; faculty_collection; sabbatical_report

Indian Buddhist Art. - Weinstein, Lucie (1990)
Keywords: dept.art; faculty_collection; sabbatical_report

[ Anasazi ] - Zeidenbergs, Olafs (1990)
Keywords: dept.art; faculty_collection; sabbatical_report

(Work in the Areas of Sculpture and Glass Research) - Pelletieri, Peter (1989)
Keywords: dept.art; faculty_collection; sabbatical_report

Catalogue of the Africana Collection, SCSU. - Pospisil, Zdenka (1989)
Keywords: dept.art; faculty_collection; sabbatical_report

(German Goldsmithing) - Rueger, Paul (1989)
Keywords: dept.art; faculty_collection; sabbatical_report

The Polite Escape: On the Myth of Secularization - Ausmus, Harry J. (Ohio University Press, 1982)
Keywords: 20th century; 20th century; Nihilism (Philosophy); History; History of doctrines; Secularization (Theology); dept.art; faculty_collection

A Schopenhauerian Critique of Nietzsche's Thought: Toward a Restoration of Metaphysics - Ausmus, Harry J. (E. Mellen Press, 1996)
Keywords: 19th century; Metaphysics; Nietzsche; Friedrich Wilhelm; 1844-1900; Schopenhauer; Arthur; 1788-1860; Philosophy; German; dept.art; faculty_collection

The Blank Canvas: Inviting the Muse - Audette, Anna Held (Shambhala, 1993)
Keywords: Artist's block; Creation (Literary; artistic; etc.); Artists; Psychology; dept.art; faculty_collection

I Bamboccianti: Niederländische Malerrebellen Im Rom Des Barock - Levine, David A.; Mai, Ekkehard; Wallraf-Richartz-Museum; Centraal Museum (Electa, 1991)
Keywords: 17th century; Exhibitions; Exhibitions; Bamboccianti (Group of artists); Exhibitions; Painting; Dutch; Exhibitions; Rome (Italy); In art; Influence; Painting; Dutch; dept.art; faculty_collection

The Pragmatic God: On the Nihilism of Reinhold Niebuhr. - Ausmus, Harry J. (1990)
Keywords: Niebuhr; Reinhold; 1892-1971; dept.art; faculty_collection

Will Herberg, from Right to Right - Ausmus, Harry J. (University of North Carolina Press, 1987)
A study of the life and thought of Will Herberg (1906-1977), a theorist in sociology and religion. A communist in the 1920s-30s, Herberg was identified in the 1950s as a moderate and an advocate of American religious pluralism, and in the 1960s as an anti-communist crusader. On pp. 81-84 shows how, after his abandonment of communism and rediscovery of Judaism, Herberg viewed antisemitism as the inevitable result of the Jew's marginal position in the world and of Judaism's witness to God's message. He contended that Christians who engaged in antisemitism were rebelling against their religion and lapsing into paganism. He condemned Soviet antisemitism and predicted the USSR's adoption of anti-Zionism. He also discussed the reasons for Black antisemitism (pp. 191-194).
Keywords: Biography; Biography; Jewish scholars; Biography; Jews; Herberg; Will; Religion historians; United States; dept.art; faculty_collection

Click, Rumble, Roar: Poems About Machines - Hopkins, Lee Bennett; Audette, Anna Held (T.Y. Crowell, 1987)
A collection of eighteen poems about machines by Myra Cohn Livingston, Eve Merriam, David McCord, and others.
Keywords: Children's poetry; American; Machinery; Juvenile poetry; American poetry; dept.art; faculty_collection

Will Herberg, a bio-bibliography - Ausmus, Harry J. (Greenwood Press, 1986)
Keywords: Bio-bibliography; Religion historians; Biography; Herberg; Will; United States; dept.art; faculty_collection

Catalog of the Professional Library of Samuel Miller Brownell: Consisting of Books and Other Publications on Education and Administration and Reports, Records, Congressional Testimony and Speeches from the Experiences of S. M. Brownell, 1927-1977. - Brownell, Samuel Miller (S. M. Brownell, 1984)
Keywords: Brownell; Samuel Miller; 1900-1990; Educators; Officials and employees; United States; Education; United States; United States; dept.art; faculty_collection

American Women Artists, Past and Present: A Selected Bibliographic Guide - Tufts, Eleanor (Garland Pub., 1984)
Keywords: Bibliography; United States; Women artists; dept.art; faculty_collection

Relations - Fussiner, Howard (published by his friends, 1983)
Keywords: dept.art; faculty_collection

A Song in Stone: City Poems - Hopkins, Lee Bennett; Audette, Anna Held (Crowell, 1983)
Twenty poems about city life by Eve Merriam, Myra Cohn Livingston, Lilian Moore, and other authors.
Keywords: City and town life; Juvenile poetry; Children's poetry; American; City and town life; Poetry; American poetry; dept.art; faculty_collection

Samuel Miller Brownell Professional Library Collection Book List. - Brownell, Samuel Miller (1978)
Keywords: Bibliography; School management and organization; dept.art; faculty_collection

Fear and Force Versus Education: A Study of the Effects of Coercion on Learning - Wieder, Charles G. (Branden Press, 1978)
Keywords: Learning; Psychology of; dept.art; faculty_collection

Louis C. Tiffany's Art Glass - Koch, Robert (Crown Publishers, 1977)
Keywords: 19th century; Decoration and ornament; Art nouveau; History; Tiffany; Louis Comfort; 1848-1933; Art glass; United States; dept.art; faculty_collection

Louis C. Tiffany Und Seine Glaskunst - Koch, Robert (Paul Haupt, 1976)
Keywords: Art nouveau; Tiffany; Louis Comfort; 1848-1933; Glassware; United States; Decoration and ornament; dept.art; faculty_collection

Complete Photo-Course Handbook - Cyr, Don (Omega Arts, 1974)
Keywords: Handbooks; manuals; etc; Photography; dept.art; faculty_collection

Our Hidden Heritage: Five Centuries of Women Artists. - Tufts, Eleanor (Paddington Press, 1974)
Keywords: Biography; Women artists; dept.art; faculty_collection

Louis C. Tiffany's Glass-Bronzes-Lamps; a Complete Collector's Guide. - Koch, Robert (Crown, 1971)
SCSU Faculty Scholar Award
Keywords: SCSU Faculty Scholar Award; Tiffany; Louis Comfort; 1848-1933; award_winner; dept.art; faculty_collection

Artistic America, Tiffany Glass, and Art Nouveau. - Bing, Siegfried (MIT Press, 1970)
Keywords: 19th century; Art; American; Art; American; dept.art; faculty_collection

Ceramic Glaze Formulas. - Crespi, David E. (Dav-Lin, 1966)
Keywords: Glazes; dept.art; faculty_collection

Louis C. Tiffany, Rebel in Glass. - Koch, Robert (Crown Publishers, 1966)
Keywords: Tiffany; Louis Comfort; 1848-1933; dept.art; faculty_collection

The Schools of Glen Ridge; a Survey Conducted by Members of the Faculty of the Department of Education of Yale University; the Survey Committee: Clyde Milton Hill ... Samuel Miller Brownell ... John Seiler Brubacher ... Bessie Lee Gambrill ... John Warren Tilton. - Yale University Department of Education (Yale, 1941)
Keywords: Glen Ridge; New Jersey; Public schools; dept.art; faculty_collection

A Second Meléndez Self-Portrait: The Artist as Still Life - Tufts, E.M. (The Art Bulletin, 1974)
0 citations (Crossref) [2023-10-31]
Keywords: dept.art

The Dilemma of the Artist-Teacher - Orsini, N. (Art Journal, 1973)
0 citations (Crossref) [2023-10-31]
Keywords: dept.art

The Roman Limekilns of the Bamboccianti - Levine, D.A. (The Art Bulletin, 1988)
Pieter van Laer and his followers — the so-called Bamboccianti — have usually been interpreted as realists or near-realists who painted simple, unassuming scenes of everyday life in seventeenth-century Rome. The testimony of their earliest critics gives us reason to suspect, however, that the Bamboccianti were actually pursuing a contrived form of painting that expressed meaning through irony and paradox. This idea is tested by examining one theme treated frequently by the artists in question — limekilns in Roman settings. By witty allusion to both the destruction and persistence of antiquity, pictures of Roman limekilns lead the viewer to contemplate a paradox regarding the nature of greatness and eternity. © 1988, College Art Association of America, Inc. All rights reserved.
0 citations (Crossref) [2023-10-31]
Keywords: dept.art

The Iconography of the St. Andrew Auckland Cross - Calvert, J. (The Art Bulletin, 1984)
4 citations (Crossref) [2023-10-31]
Keywords: dept.art

Art of Renaissance in Eastern-Europe - Hungary, Bohemia, Poland - Bialostocki,j - Pospisil, Z (Slavic and East European Journal, 1977)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1977DV24800035
Keywords: dept.art

Technology in the elementary art room - Girardi, Sydney K P (1999)
Citation Key Alias: lens.org/094-337-025-777-064
Keywords: dept.art

Nothing but history: Reconstruction and extremity after metaphysics - Roberts,DD - Ausmus, HJ (American Historical Review, 1997)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1997XF45600010
Keywords: dept.art

Review of Weltgericht Oder Revolution: Protestantische und Sozialistische Zukunftsvorstellungen im Deutschen Kaiserreich, Lucian Hölscher - Ausmus, Harry J. (The American Historical Review, 1991)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1991EZ34100100 tex.unique-id: [object Object]
Keywords: dept.art